UPAYA GURU TERHADAP RENDAHNYA MINAT BELAJAR PESERTA DIDIK KELAS VII DALAM PEMBELAJARAN IPS DI PONTIANAK - Yulianus Riko; Aminuyati Aminuyati; Yusawinur Barella (Universitas Tanjungpura, 2023)
This research is aimed to determine the teacher's efforts towards the low learning interest of class VII C students at SMP Negeri 2 Pontianak. The research approach used is descriptive qualitative research. The data sources used are primary and secondary data. Primary data included teachers and students in class VII C at SMP Negeri 2 Pontianak, and secondary data was in the form of documentation in the field. Data collection techniques used in this study were observation, interviews, and documentation. The tool used for documentation is a mobile camera. From this study, the results showed that the low learning interest of class VII C students in social studies learning at SMP Negeri 2 Pontianak was influenced by the readiness, interest, attention, and less effort of students. The teacher's efforts to increase the learning interest of class VII C students in social studies learning at SMP Negeri 2 Pontianak included: 1. using several books as a source of teaching materials, and 2. using various learning methods